Demand for Financial Service in Capital Market of Nepal - Dhungana, Ajaya; Devkota, Tej Prasad (Quest Journal of Management and Social Sciences, 2021)
Background: In the contemporary literature, access to finance is well spell-out as the key to development. The supply leading hypothesis asserts that financial deepening contributes to enhancing growth so, the growth of the financial market is regarded as an important infrastructure to influence saving and investment. The Government of Nepal opted for a policy ‘One person one bank account’ in its fiscal policy in 2018/19 (MOF, 2018). Aligning the policy, the Securities Board of Nepal (SEBON) launched the ‘one Nepali one D-mat account’ policy in 2018 to increase the access of the capital market throughout the country. The low-financial literacy base is a major constraint to develop the market, in the other, most of the rural population, still are not equipped with the capital market instrument. In, this background, there is an utmost need to examine the factors contributing the demand for the financial services. Objective: The primary objective of the study is to access the determinants of the demand for financial services in the capital market of Nepal, considering the supply leading hypothesis. Method: To examine the determinants of the demand for financial service, we employed the Ordinary Least Square method of regression analysis. The dependent variable employed in this study is the demand for financial services. Level of income, access to finance and financially active provinces have been taken as the independent variable along with the concerned district population. As well, the financial literacy program conducted by the capital market regulator is another major independent variable. Result: The demand following hypotheses asserts that financial literacy is the key to influence the demand for financial services. It is found that financial literacy programs conducted by the capital market regulator could not explain the demand for financial services in Nepal indicating the weak performance of the program conducted by SEBON. It is found that the number of BFIs, population and financially active provinces are highly significant with the demand for financial services indication the influential role of supply leading hypothesis. Conclusion: The study concludes that the variables selected to determine the demand for financial services in capital market are appropriate and most of them (population, per capita income, financially active provinces and access to financial services) are significant with the capital market of Nepal. It is observed that the financial literacy programs conducted by the capital market regulator have not contributed in enhancing demand of the financial services in the capital market of Nepal. Recommendation: The study is focused and based on the capital market of Nepal. Results obtained from this study could not replicate the same in the money market or insurance sector of Nepal. The findings of the study strongly recommend the regulatory body to evaluate and revise its financial literacy programs while in the meantime urge to focus on addressing demand-side inefficiencies in the long run. Originality: The research work is original and has not been published in other publications. As well, no financial support has been received for the study.